Turats Book Teacher's Strategy in Improving Students' Learning Achievement at Baitul Buku Campus III Bulu Lampang DDI Mangkoso Islamic Boarding School - Nuraeni; St. Nurhayati; Marhani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Baitul kitab is a non-formal institution that has long been implemented in Islamic boarding schools, starting in 2015. This research is qualitative research using case study research, the data type uses subject data and the data sources are Baitul kitab teachers and students. The next stages of data collection used were observation, in-depth interviews and documentation. Data analysis includes data reduction, data presentation and drawing conclusions and verification. And the data validity testing techniques used are the credibility test and dependability test. The results of the research show that: 1) The strategy of the turats teacher in the process of implementing learning in Baitul kitab includes: Using the Sorogan, Bendongan, Mudzakarah, Question and answer, memorizing methods and the teacher prepares a learning plan according to the students' level of understanding, this is divided into three levels including level A (high), level B (medium) and level C (low). A teacher prepares several methods in order to understand the level of ability of the students, 2) the steps carried out by the teacher of the book of turats, the author has seen directly in the baitul kitab, he has carried out the study of the book of turats in accordance with established procedures in order to be able to improve the learning achievement of the students of the Baitul kitab. 3) factors that influence improving the learning achievement of students in Baitul kitab, time factors, students, teachers, environment and facilities and infrastructure in learning the turats book.